Osebna in objektivna bibliografija Lojzeta Novaka - Horvat, Sara (Knjižnica, 2012)
Purpose: The article explores the life and work of the Slovenian author Lojze Novak in order to get more recognition of the author in Slovenia. The articleinitially deals with the publishing activities of Argentina's diaspora. Methodology/approach: ln order to create the bibliography the following bibliographic meth- ods were used: searching and collecting the Novaks works, bibliographic description as well as the arrangement of his opus. Novak' s works were obtained from Argentina, specifically from the TineDebeljak legacy, Novak's descendants, his contemporaries, friends and acquaintances, and from the National and University Library (NUK). Bibliographic descriptions are based on the primary documents therefore the data are accurate and verified. Bibliographic descriptions follow the Guidelines for the application of the ISBDs to the description of component parts (1998). Novak's personal bibliography includes 60 units arranged into published (52) and unpublished (8) works. Published works which consist of works of fiction (46) and nonfiction (6) are arranged chronologically by the publication year whereas within each year they are organised alphabetically. Novaks biobibliography which includes 6 works and is arranged chronologically has also been produced through this process. Results: Since the author Lojze Novak has not won recognition in Slovenia yet, he has been introduced to our country by the personal bibliography and biobibliography that resulted from this research. Originality/practical implications: By doing the research into Novaks opus eight of his unpublished works in manuscript form were discovered and included in his primary personal bibliography. It is therefore a comprehensive bibliography in the field.
Keywords: bibliografije; Lojze Novak (1927-1986); objektivne bibliografije; osebne bibliografije; Slovenci v Argentini